Relaxed inertial methods for solving the split monotone variational inclusion problem beyond co-coerciveness. (1st February 2023) - Izuchukwu, Chinedu; Reich, Simeon; Shehu, Yekini
Abstract : We study the split monotone variational inclusion problem in two real Hilbert spaces. Combining the inertial and relaxation techniques with the proximal contraction algorithm, we propose two new methods for solving this problem without the usual co-coerciveness assumption on the associated operators.